Introduction of Crossbar Switching Equipment to the Australian Telephone Network - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2018)
A historic paper from the Journal in 1961 summarising the investigation and selection of Crossbar Switching Equipment for the Australian Telephone Network.